2003
DOI: 10.1016/s0195-668x(02)00468-2
|View full text |Cite
|
Sign up to set email alerts
|

Long distance transport for primary angioplasty vs immediate thrombolysis in acute myocardial infarction Final results of the randomized national multicentre trial—PRAGUE-2

Abstract: Long distance transport from a community hospital to a tertiary PCI centre in the acute phase of AMI is safe. This strategy markedly decreases mortality in patients presenting >3 h after symptom onset. For patients presenting within <3 h of symptoms, TL results are similar results to long distance transport for PCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
309
0
51

Year Published

2003
2003
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 690 publications
(372 citation statements)
references
References 24 publications
9
309
0
51
Order By: Relevance
“…This is also well within the 110 min to 114 min PCI-related delay at which primary PCI is expected to lose its mortality benefit over thrombolytic therapy (13,14). On the other hand, the 110 min estimated PCI-related delay for patients transferred from remote hospitals was longer than in previous randomized clinical trials (3,4). In the present study, DTB times were shorter for patients presenting during normal business hours than for patients presenting during weekends or outside normal duty hours.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This is also well within the 110 min to 114 min PCI-related delay at which primary PCI is expected to lose its mortality benefit over thrombolytic therapy (13,14). On the other hand, the 110 min estimated PCI-related delay for patients transferred from remote hospitals was longer than in previous randomized clinical trials (3,4). In the present study, DTB times were shorter for patients presenting during normal business hours than for patients presenting during weekends or outside normal duty hours.…”
Section: Discussionsupporting
confidence: 79%
“…Many studies have shown that transferring STEMI patients is safe, and that the benefits of primary PCI over thrombolytic therapy are conserved when transfer delays are reasonable (2)(3)(4)(5). Based on randomized, controlled trials, the current guidelines for STEMI recommend a door-to-balloon (DTB) time of less than 90 min when performing primary PCI, including transfer time (6)(7)(8).…”
mentioning
confidence: 99%
“…Although the authors propose that emergency hospital transfer is both feasible and safe, a 1.2% complication rate amongst transported patients was recently reported in the Primary Angioplasty in patients transferred from General community hospitals to specialized PTCA Units with or without Emergency thrombolysis 2 (PRAGUE 2) study, in which 2 patients died and 3 developed ventricular fibrillation. 22 In our view, this analysis is Figure 1. The evolution of timing and location for administration of fibrinolytic therapy.…”
Section: Choice Of Reperfusion Strategymentioning
confidence: 95%
“…1,[15][16][17] The present findings of a different outcome of the comparison between thrombolysis and primary PCI as a function of time from onset of symptoms are consistent with results from the PRAGUE II trial, in which in-hospital thrombolysis achieved identical 30-day mortality compared with primary PCI within the first 3 hours after symptom onset (7.4% versus 7.3%, respectively), whereas mortality was lower with PCI among patients randomized later. 18 In the Zwolle randomized trial of thrombolysis versus primary PCI, the latter was associated with lower adverse event rates regardless of Values are number of patients (%) or median (interquartile range; 25th and 75th percentiles). *P for heterogeneity.…”
Section: Steg Et Al Prehospital Rtpa Vs Primary Pcimentioning
confidence: 99%